Structure restoration and coarsening of nanocrystalline cementite in cold drawn pearlitic wire induced by low temperature annealing. (1st July 2022) - Zhou, Lichu; Fang, Feng; Kumagai, Masayoshi; Pickering, Ed; Yu, Tianbo; Zhang, Xiaodan
Abstract: Internal structure of nano-scale cementite has exhibited a critical impact on mechanical performance for various heavily strained high-carbon steel materials. Through a combination of post-annealing and in-situ annealing transmission electron microscopy observations, we investigated the structural evolution of heavily strained cementite during low-temperature annealing. During annealing, the morphology of the cementite lamellae is stable when the temperature ( T a ) is lower than 350 °C. Meanwhile, lattice structure restoration and coarsening of nanocrystalline cementite ( θ -NC) occur. Cementite lamellae, with a nanocrystalline structure in the as-drawn state were observed to transform into a coarsened isometric shape θ -NC (140 °C < T a < 210 °C) or elongated θ -NC (210 °C < T a < 350 °C). The coarsening activation energy of heavily strained cementite nanocrystals in the lamellae is estimated to be in a range of 37–50 kJ mol −1 . The coarsening behavior is limited by the ferrite-cementite phase boundary. Graphical abstract: Image, graphical abstract